2018
DOI: 10.1016/j.appet.2017.11.107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of feeding tube dependency with respect to food aversive behaviour and growth

Abstract: The use of feeding tubes in pediatric medical procedures and management has dramatically increased over the last three decades. With this increase, the prevalence of Feeding Tube Dependency (FTD) - a reliance on enteral feeding following medical recovery due to lack of oral intake of nutrition, despite being able to eat- has increased too. It has been suggested, that cases with FTD show avoidant feeding behaviours such as food refusal, gagging or swallowing resistance, but evidence for this hypothesis is scarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Dunitz‐Scheer et al () also reported an impaired quality of life, but did not mention if and how the quality of life had been measured. Since tube feeding can impact health and psychosocial functioning in children, we suspected that ARFID patients receiving tube feeding, would also have lower HRQOL subscales (Benoit et al, ; Hartdorff et al, ; Krom et al, ; Krom et al, ; Wilken et al, ). However, no significant differences were found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dunitz‐Scheer et al () also reported an impaired quality of life, but did not mention if and how the quality of life had been measured. Since tube feeding can impact health and psychosocial functioning in children, we suspected that ARFID patients receiving tube feeding, would also have lower HRQOL subscales (Benoit et al, ; Hartdorff et al, ; Krom et al, ; Krom et al, ; Wilken et al, ). However, no significant differences were found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that our tertiary care center has a large NICU ward, and is an expert center for certain genetic diseases and syndromes contributed to our popula- (Eddy et al, 2015;Fisher et al, 2014;Norris et al, 2016). Additionally, the diversity within the ARFID population may be attributed to the chronic medical conditions and/or development delays associated with feeding issues (Bryant-Waugh, Markham, Kreipe, & Walsh, 2010;Rommel, de Meyer, Feenstra, & Veereman-Wauters, 2003;Wilken et al, 2018). As such, the DSM-5 criteria do not exclude patients with the aforementioned comorbidities from the ARFID diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early screening for nutrition deficiencies and targeted nutrition therapy may improve outcomes and quality of life for transplant recipients . The nutrition therapy utilized pre‐, peri‐, and post‐transplantation may have the adverse effect of impeding normally developing feeding skills, particularly in very young children . Yet, little is known about the feeding and nutrition habits of pediatric transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…16 The nutrition therapy utilized pre-, peri-, and posttransplantation may have the adverse effect of impeding normally developing feeding skills, particularly in very young children. 17,18 Yet, little is known about the feeding and nutrition habits of pediatric transplant recipients. The current study investigates severity of feeding disorder and parental stress among patients seen at the Children's Hospital of Wisconsin's FSNC that had received a transplant with feeding-disordered patients who did not and the general community.…”
Section: Introductionmentioning
confidence: 99%